EFFECT OF THE MYCELIUM EXTRACT FROM DUDDINGTONIA FLAGRANS FUNGUS ON SUBCUTANEOUS XENOGRAFT OF HUMAN C33a CERVICAL CARCINOMA CELLS - O. I. Solovieva (Sibirskij Onkologičeskij Žurnal, 2020)
The purpose of the study was to analyze the antitumor effects of the extract of mycelium from Duddingtonia flagrans (strain F-882) on xenografts of human C33a cervical cancer cells.Material and Methods. To evaluate the antitumor effect, we used the absolute values of xenograft volumes and calculated the tumor growth inhibition and the index of tumor growth.Results. At the first stage of the experiment, a 4-week subcutaneous injection of the water extract of F-882 resulted in an almost twofold slowdown in xenograft growth, with the tumor growth inhibition value of 50.6 %. In the second stage of the experiment, a 2.5-week subcutaneous injection followed by a 1.5-week intratumoral injection of F-882 also caused the tumor growth inhibition. After completing F-882 injections, the effect of tumor growth inhibition continued for 2.5 weeks and the tumor growth inhibition value was 58.7 %.Conclusion. The mycelium extract F-882 was shown to have an antitumor effect on subcutaneous xenografts of human C33a cervical carcinoma cells.